Why do T cells express the vitamin D receptor? - Cantorna, Margherita T. (2010)
Vitamin D is an important regulator of immune function. T cells express the vitamin D receptor (VDR) and have been shown to be direct and indirect vitamin D targets. Why should T cells be responsive to vitamin D? The data suggest that expression of the VDR is required for the development of two cells types, NKT cells and CD8αα T cells, that inhibit autoimmunity. In addition, effector T cell cytokine production is regulated by vitamin D. I propose that NKT and CD8αα T cells express the VDR as part of the selection process to protect against the generation of autoimmunity, particularly in the gut.